2021
DOI: 10.2478/sjph-2021-0033
|View full text |Cite
|
Sign up to set email alerts
|

Students in danger: Binge drinking behaviour and associated factors in Hungary

Abstract: Introduction Among young adults, high rates of binge drinking were observed in certain European countries. Binge drinking is associated with several health problems (unplanned pregnancy, HIV infections, problems with memory, and injuries). The aim of this questionnaire-based study was to measure the frequency of binge drinking and its association with sociodemographic, familial, lifestyle factors and school performance among secondary and university students (n=2449) in Csongrád County, Hunga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Alcohol is the most frequently consumed substance among young adults, including those with severe obesity 29 . Furthermore, when young adults consume alcohol, they typically drink more per occasion than adults (ie, BD), and 16% also consume other drugs 30,31 . Alcohol use, and BD in particular, are primary contributors to the leading cause of death and/or unintentional injury (including attempting suicide) in young adults 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol is the most frequently consumed substance among young adults, including those with severe obesity 29 . Furthermore, when young adults consume alcohol, they typically drink more per occasion than adults (ie, BD), and 16% also consume other drugs 30,31 . Alcohol use, and BD in particular, are primary contributors to the leading cause of death and/or unintentional injury (including attempting suicide) in young adults 32 .…”
Section: Discussionmentioning
confidence: 99%
“… 29 Furthermore, when young adults consume alcohol, they typically drink more per occasion than adults (ie, BD), and 16% also consume other drugs. 30 31 Alcohol use, and BD in particular, are primary contributors to the leading cause of death and/or unintentional injury (including attempting suicide) in young adults. 32 Among patients with severe obesity, both binge behaviors (drinking and eating) frequently co-exist.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, younger participants reported significantly higher anxiety scores than older participants. Interestingly, a recent study ( 51 ) on binge drinking found that this risky behaviour is very common among young adults. Because the term ‘binge’ refers not only to eating but also to extreme and uncontrolled activities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, alcohol has been an outlet for thrill seeking and involves relieving boredom [103,104], and boredom has also been found to be a predictor of gambling motivation [105]. Finally, within these social factors, these binge consumption patterns are commonplace in Western society, as reflected by the elevated or increasing prevalence rates of most common binge behaviors such as binge drinking (18.2%) [44,106], binge eating (0.3% to 4.5%) [41,45], or binge watching (72%) [107], among others.…”
Section: Psychological Cognitive and Social Factors Related To Binge ...mentioning
confidence: 99%